Exploring sketches as conceptual data: a semiological experiment on moods visualisation among architectural students - Abd Manan, Mohd Shahrudin; Kennedy, Blakely (Emerald Group Publishing, 2021)
Purpose – Sketching is a creative skill that most architects develop over their long period of study and is considered an effective medium for communicating imaginative thinking and conceptual ideas in architecture. As a concept, mood is generally associated with imagining specific ambiance and spatial experience during the schematic phase of the architectural design process. While most architectural research on mood revolves around post-occupancy evaluation, colour effect and lighting comfort, few studies have been conducted to systematically investigate conceptual issues related to mood imagination. Besides, there has been little attempt to appreciate sketches as a reliable conceptual data source for architectural research. Design/methodology/approach – To bridge this knowledge gap, this paper explores a semiological analysis of mood visualisation using architectural sketches. By framing the experiment within the architecture education context, the paper begins by discussing the relationship between sketching, mood and semiology in architecture. The discussion continues by highlighting methodological issues in the design of our experiment. The experiment comprised architecture students from undergraduate and postgraduate programmes. Following the visual and textual data derived from the experiment, two semiological analyses, namely, mood sign analysis and mood signifier analysis, were conducted to understand their imaginative thinking. Findings – The results revealed significant preferential differences between the students on the use of specific semiotic representation and design language to conceptualise their mood idea. Originality/value – As a preliminary experiment, this study constitutes an early attempt to further explore potential research related to architectural sketches and the creative imagination that may be beneficial to designers, art psychologists, educators and researchers alike.